Handbook of research on the impacts, challenges, and policy responses to overtourism - Almeida, Cláudia Ribeiro de 1971-; Quintano, Alfred; Simancas, Moisés; Huete, Raquel (Advances in hospitality, tourism, and the services industry book series, 2020)
"This book is a collection of research on best practices and legislation solutions for the management of tourism destinations suffering from overtourism, tourismophobia, or antitourism movement issues"--